Reporting Wandering Dogs to Protect Kiwi and Dogs: New Zealanders’ Involvement, Attitudes, and Beliefs - Anne C. Macaskill; Geoff Kaine; Joanne P. Aley (Conservation)
Wandering dogs are a threat to Aotearoa New Zealand’s endemic kiwi bird species because kiwi have not evolved defenses against mammalian predators. New Zealanders can protect kiwi by reporting wandering dogs, and this also protects the dogs themselves. This study explored New Zealanders’ reporting intentions and behavior, as well as attitudes and beliefs about wandering dogs, harm to kiwi, and dog welfare. Guided by the I3 framework, we also assessed respondents’ involvement with the intervention of reporting, and involvement with both dog welfare and kiwi welfare. A sample of 250 New Zealanders completed the questionnaire online. Attitudes and behavior were consistent with involvement, and patterns for involvement with kiwi welfare and involvement with dog welfare were similar. The results indicated that almost all respondents fell into one of two quadrants based on involvement—both quadrants were highly involved with dog and kiwi welfare but varied on involvement with reporting. This pattern suggests that promotion campaigns are likely to be an effective intervention to increase the reporting of wandering dogs. Promotional campaigns might focus on dog welfare or kiwi welfare, and should highlight the link between reporting, dogs, and harm to kiwi.